(Il)legality and psychosocial well-being: Central Asian migrant women in Russia. Issue 1 (2nd January 2022) - Agadjanian, Victor; Oh, Byeongdon; Menjívar, Cecilia
ABSTRACT: Legal status has shown far-reaching consequences for international migrants' incorporation trajectories and outcomes in Western contexts. In dialogue with the extant research, we examine the implications of legal status for psychosocial well-being of Central Asian migrant women in the Russian Federation. Using survey data collected through respondent-driven sampling in two large cities, we compare migrants with regularised and irregular legal statuses on several interrelated yet distinct dimensions of psychosocial well-being. We find that, regardless of other factors, regularised status has a strong positive association with migrants' perception of their rights and freedoms but not with their feeling of being respected in society. Regularised status is positively associated with self-efficacy and negatively with depression. Yet, no net legal status difference is found in migrants' views on their relations with other migrants or on treatment of migrants by native-borns. The findings are situated within the cross-national scholarship on the ramifications of racialized immigrant (il)legality and its implications for membership and belonging.